Evaluation of hyper-attenuated S19 poliovirus strains for use in poliovirus neutralization assays - Nicholas Wiese; William Hendley; Basit Jafri; Kathryn A.V. Jones; Giovanna Sifontes; Sandra Valdez; Yiting Zhang; Bernardo A. Mainou (PLoS ONE, 2026)
Poliovirus eradication efforts have relied on effective vaccination campaigns and stringent laboratory containment of poliovirus strains. Serological testing is the primary means to address population immunity, vaccine efficacy, and individual poliovirus exposures. However, strict containment requirements for Sabin type 2 and wild poliovirus types 2 & 3 limit access to serological testing. To address these limitations, we evaluated the performance of hyper-attenuated, temperature-sensitive S19 poliovirus strains (S19-PV), which retain the antigenic characteristics of Sabin and Salk strains but can be handled under biosafety level 2 (BSL-2) conditions. Using a modified microneutralization assay, we performed a comparative validation of S19-PVs to their Sabin and wild-type counterparts using WHO international standards, in-house control reagents, and human sera. Neutralizing antibody titers showed strong concordance between S19-PV and reference strains (R² = 0.93–0.99), with high intra- and inter-assay reproducibility (CVs < 10%). Our findings demonstrate that S19-PV strains are antigenically equivalent to Sabin and wild-type viruses and suitable for use in neutralization assays to determine levels of poliovirus neutralizing antibodies outside of strict containment laboratories. Adoption of these strains can significantly expand global capacity for poliovirus serological testing, supporting surveillance and immunization activities in the final stages of poliovirus eradication.